2003
DOI: 10.1021/bi034490u
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Dynamics of the Lantibiotic Mutacin 1140

Abstract: Mutacin 1140 is a member of a family of ribosomally synthesized peptide bacteriocins called lantibiotics (lanthionine-containing antibiotics) and is produced by the Gram-positive bacterium Streptococcus mutans. Mutacin 1140 has been shown to be effective against a broad array of Gram-positive bacteria. Chromatography and mass spectroscopy data suggested that mutacin 1140 forms a small compact structure. Nuclear magnetic resonance (NMR) data and restrained molecular dynamics simulations showed that mutacin 1140… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
52
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 32 publications
1
52
0
Order By: Relevance
“…The crude extract was run on either a semiprep C 18 column (octyldecyl silane [C 18 ]; particle size, 5 m; 4.6 by 250 mm; Agilent Zorbax) or an analytical column, as previously reported (35). 2-Mercaptoethanol (BME) modification of mutacin 1140 peptide variants was done as previously reported (13,36). The lack of PTM cyclase activity would prevent lanthionine ring formation and result in the presence of cysteine thiols that can be selectively labeled.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The crude extract was run on either a semiprep C 18 column (octyldecyl silane [C 18 ]; particle size, 5 m; 4.6 by 250 mm; Agilent Zorbax) or an analytical column, as previously reported (35). 2-Mercaptoethanol (BME) modification of mutacin 1140 peptide variants was done as previously reported (13,36). The lack of PTM cyclase activity would prevent lanthionine ring formation and result in the presence of cysteine thiols that can be selectively labeled.…”
Section: Methodsmentioning
confidence: 99%
“…Mutacin 1140 and nisin have structurally similar rings A and B (Fig. 1A), and both nisin and mutacin 1140 bind and abduct lipid II (8)(9)(10)(11)(12)(13). Mutacin 1140 has also been shown to be bactericidal to pathogenic bacteria, such as methicillin-resistant Staphylococcus aureus (MRSA), with no significant development of resistance (14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Work performed by Smith et al using the membrane mimetic solvent acetonitrile/water (80 :20) showed that mutacin 1140 has an overall horseshoe-like shape that is kinked at the "hinge region" between rings B and C (20). This shape is the result of a turn-like motif in the hinge region that folds the N-terminal rings A and B (the lipid II binding domain) toward the C-terminal overlapped rings C and D (20).…”
mentioning
confidence: 99%
“…This shape is the result of a turn-like motif in the hinge region that folds the N-terminal rings A and B (the lipid II binding domain) toward the C-terminal overlapped rings C and D (20). Interestingly, the flexibility of the hinge region is believed to be important for promoting lateral assembly of mutacin 1140 monomers.…”
mentioning
confidence: 99%